A zero coronary artery calcium score in patients with stable chest pain is associated with a good prognosis, despite risk of non-calcified plaques. Issue 1 (11th April 2019) - Wang, Xue; Le, Elizabeth Phuong Vi; Rajani, Nikil K; Hudson-Peacock, NJ; Pavey, Holly; Tarkin, Jason M; Babar, Judith; Williams, Michelle Claire; Gopalan, Deepa; Rudd, James H F
Abstract : Objectives: To estimate the prevalence of non-calcified coronary artery disease (CAD) in patients with suspected stable angina and a zero coronary artery calcification (CAC) score, and to assess the prognostic significance of a zero CAC in these symptomatic patients. Methods: In this prospective cohort study, consecutive patients with stable chest pain underwent CAC scoring ± CT coronary angiography (CTCA) as part of routine clinical care at a single tertiary centre over 7 years. Major adverse cardiac event (MACE) was defined as cardiac death, non-fatal myocardial infarction and/or non-elective revascularisation. Results: A total of 915 of 1753 (52.2%) patients (mean age 56.8 ± 12.0 years; 46.2% male) had a zero CAC score. Of the 751 (82.1%) patients with a zero CAC in whom CTCA was performed, 674 (89.7%) had normal coronary arteries, 63 (8.4%) had non-calcified CAD with < 50% stenosis and 14 (1.9%) had ≥ 50% stenosis in at least one coronary artery. The negative predictive value of a zero CAC for excluding a ≥ 50% CTCA stenosis was 98.1%. Over a median follow-up period of 2.2 years (range 1.0–7.0 years), the absolute annualised rates of MACE were as follows: zero CAC 1.9 per 1000 person-years and non-zero CAC 7.4 per 1000 person-years (HR 3.8, p = 0.009). However, after adjusting for age, gender and cardiovascular risk factors using a multivariable Cox proportional hazards model, there was no statistically significant difference in the risk of MACE between the two patient cohorts (p = 0.19). After adjusting for age, gender and cardiovascular risk factors, the HR for all-cause mortality among the zero CAC cohort vers non-zero CAC was 2.1 (p = 0.27). Conclusion: A zero CAC score in patients undergoing CT scanning for suspected stable angina has a high negative predictive value for the exclusion of obstructive CAD and is associated with a good medium-term prognosis.